Effect of Dietary Fiber Intake on Blood Sugar Levels in Kenya - Makori, Irene (American Journal of Food Sciences and Nutrition, 2024)
Purpose: The aim of the study was to investigate the effect of dietary fiber intake on blood sugar levels in Kenya. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Studies on dietary fiber intake in Kenya suggest that higher fiber consumption is linked to better blood sugar control, reduced glycemic responses, and improved insulin sensitivity. Traditional Kenyan diets, rich in fiber from whole foods like grains, legumes, fruits, and vegetables, play a significant role in promoting these health benefits. These findings emphasize the potential of dietary fiber in managing blood sugar levels and preventing diabetes in Kenya, highlighting the importance of encouraging fiber-rich dietary patterns in public health strategies. Implications to Theory, Practice and Policy: The glycemic index (GI) theory, the gut microbiota theory and the insulin resistance theory may be use to anchor future studies on the effect of dietary fiber intake on blood sugar levels in Kenya. Promote Dietary Education: Healthcare practitioners should prioritize dietary education and guidance for individuals with type 2 diabetes or those at risk. Policymakers should consider integrating specific recommendations on fiber intake into national dietary guidelines.